Semi‐Transparent, Pixel‐Free Upconversion Goggles with Dual Audio‐Visual Communication - Chun‐Jen Shih; Chao‐Yang Lin; Kai Chen; Nurul Ridho Al Amin; Dian Luo; I‐Sheng Hsu; Abdul Khalik Akbar; Sajal Biring; Chih‐Hsuan Lu; Bo‐Han Chen; Shang‐Da Yang; Jiun‐Haw Lee; et al. (Advanced Science, 2023)
Abstract The intractable brittleness and opacity of the crystalline semiconductor restrict the prospect of developing low‐cost imaging systems. Here, infrared visualization technologies are established with large‐area, semi‐transparent organic upconversion devices that bring high‐resolution invisible images into sight without photolithography. To exploit all photoinduced charge carriers, a monolithic device structure is proposed built on the infrared‐selective, single‐component charge generation layer of chloroaluminum phthalocyanine (ClAlPc) coupled to two visible light‐emitting layers manipulated with unipolar charges. Transient pump‐probe spectroscopy reveals that the ClAlPc‐based device exhibits an efficient charge dissociation process under forward bias. This process is indicated by the prompt and strong features of electroabsorption screening. Furthermore, by imposing the electric field, the ultrafast excited state dynamic suggests a prolonged charge carrier lifetime from the ClAlPc, which facilitates the charge utilization for upconversion luminance. For the first time, >30% of the infrared photons are utilized without photomultiplication strategies owing to the trivial spectrum overlap between ClAlPc and the emitter. In addition, the device can broadcast the acoustic signal by synchronizing the device frequency with the light source, which enables to operate it in dual audio‐visual mode. The work demonstrates the potential of upconversion devices for affordable infrared imaging in wearable electronics.